2012
DOI: 10.5923/j.ajmms.20110101.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective and Anticancer Properties of Aqueous Olive Leaf Extract in Chemically Induced Hepatocellular Carcinoma in Rats

Abstract: Objectives: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide. We aimed to test the role of aqueous olive leaf extract (AOLE) in modulating metabolic disorders occurring in hepatic malignancy induced by trichloroacetic acid (TCA). Design: Eight groups of rats were assigned as follows: First, untreated normal control. Second, treated with 5-fluorouracil (5-FU), (75mg/kg), intraperitoneally (IP) once weekly for 3 weeks. Third, treated with oral AOLE (500mg/kg) once daily for 28 days. The 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…Treatment with olive leaves extract significantly reduced serum AFP that may indicate the curative effect of OLE which was attributed to its polyphenol and flavonoids. This result is in accordance with Abdel-Hamid et al (2011) who reported that administration of olive leaves extract significantly decreased the elevation in alpha feto protein (AFP) in hepatotoxicity rats induced by Trichloroacetic acid (TCA).The present finding was confirmed by histopathological alteration of liver in rats treated with paracetamol showing multiple focal area of necrotic hepatocytes infiltrated with mononuclear cells. The elevated level of MDA is in accordance with previous study of Farghaly and Hussein (2010), which showed the association between PCM toxicity and MDA.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with olive leaves extract significantly reduced serum AFP that may indicate the curative effect of OLE which was attributed to its polyphenol and flavonoids. This result is in accordance with Abdel-Hamid et al (2011) who reported that administration of olive leaves extract significantly decreased the elevation in alpha feto protein (AFP) in hepatotoxicity rats induced by Trichloroacetic acid (TCA).The present finding was confirmed by histopathological alteration of liver in rats treated with paracetamol showing multiple focal area of necrotic hepatocytes infiltrated with mononuclear cells. The elevated level of MDA is in accordance with previous study of Farghaly and Hussein (2010), which showed the association between PCM toxicity and MDA.…”
Section: Discussionsupporting
confidence: 93%
“…Olea europaea leaves contain maslinic acid, ursolic, oleanolic, quercetin, apigenin, luteolin, tannins, and caffeic acid [122]. Treatment of experimental animals with Olea europaea leaves extract caused a reduction in blood glucose [123], and blood pressure [124], prevention of hepatotoxicity [125,126], prevention of tumor formation [127] and suppressed inflammatory reactions [128]. Eidi et al, [129] reported that treatment of diabetic rats with Olea europaea leaf extract caused a reduction in the serum levels liver enzymes [129].…”
Section: Olive (Olea Europaea)mentioning
confidence: 99%
“…In hepatic tumours, haemolysis (plus deranged liver function) leads to hyperbilirubinemia. In the present investigation, TCA-intoxicated rats showed a significant elevation in the levels of total serum bilirubin compared to the control group which may be due to the hepatocellular or obstructive jaundice in HCC (Abdel-Hamid et al, 2011). After treatment with the AJ extract either independently (G3) or in combination with the CTX drug (G5), a reduction in T.BiL level was observed due to therapeutic and hepatoprotective efficacy of alkaloids and flavonoids in the AJ extract.…”
Section: Discussionmentioning
confidence: 45%